Reliability and maintainability analysis : a case study of production line in process tyre industry - Khairul Annwar B ABD Rahman (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Reliability and maintainability analysis is use to ensure adequate performance of the system based consistently with minimalmaintenance costs. Both combinations determine on how the proportion of time for use or matter is operating in a safe state. The aim of this project is to identify maintanability and reliability characteristics on critical machines in tyre production line with respect to repair frequency and duration .